The effectiveness of applying suggestopedia method towards reading skill - Bambang Sumadyo; Rr. Astri Indriana Octavita; Rima Novia Ulfa; Bambang Perkasa Alam (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The application of the suggestopedia method is one of the steps to create a learning climate for students’ reading skill. The application of this method is considered successful and suitable to be applied online during a pandemic because of its effectiveness in being able to provide a sense of comfort to students in the learning process in comprehending reading text. By applying quantitative research methods, there are 120 population, having 52 students as sample for being given a treatment and the same amount for being controlled. This research is able to prove that applying suggestopedia method is effective for students’ reading skill. This study was conducted to determine the effectiveness of the suggestopedia method’ application and the results is T observe 14,25925926 and T table is 1, 6755905025. According to the theory the proven score considered effective in the application of suggestopedia method on students’ reading skill.Keywords: Effect, suggestopedia method, reading skill.